A Case of Congenital Brainstem Oligodendroglioma: Pathology Findings and Review of the Literature - Stefan Kostadinov; Suzanne de la Monte (Case Reports in Neurological Medicine)
Congenital and perinatal primary brain neoplasms are extremely rare. Brainstem neoplasms in the perinatal and neonatal period are typically of high-grade nature and have poor prognoses with survival rates of less than 2 years from diagnosis. Herein, we report an unusual case of congenital anaplastic oligodendroglioma that arose in the pons and was detected as diffuse pontine glioma on in utero imaging studies during prenatal evaluation at 26 weeks’ gestation. A male infant was delivered at 36.4 weeks of gestation via Cesarean section who developed progressive dyspnea shortly after birth. Magnetic resonance imaging (MRI) studies of his head showed the expansile, poorly demarcated mass in the pons with minimal heterogeneous enhancement and severe communicating hydrocephalus. Despite aggressive management, including dexamethasone treatment, the infant expired on the third day of postnatal life. On postmortem examination cut sections through the brainstem and cerebellum disclosed the neoplasm that infiltrated the entire pons, extended into the midbrain, medulla, cerebellar peduncles, and caudal diencephalon. Histological sections demonstrated an anaplastic oligodendroglioma infiltrating the pons, 4th ventricle, midbrain, medulla, cerebellar white matter, posterior thalamus, and occipital white matter. The pathological features of the lesion distinguish it from previous reports in which spontaneous regression of pontine gliomas occurred and argue in favor of establishing a tissue diagnosis to plan for aggressive versus conservative management.